INFLUENCE OF JOB ANALYSIS (JOB ANALYSIS) ON EMPLOYEE PERFORMANCE AT PT. HAYATI PRATAMA MANDIRI WEST SUMATRA - Hendri faesal; Hendra Lukito (JURNAL STIE SEMARANG, 2019)
This study aims to determine and analyze the Effect of Job Analysis (Job Analysis) On Employee Performance On PT.Hayati Pratama Mandiri West Sumatra. This research is exploratory research with research sample that is as much as 186 people. This study uses multiple regression analysis with the help of SPSS program version 22.00 with the results of research that is 1) Job description has a positive and significant impact on employee performance in PT.Hayati Pratama Mandiri West Sumatra. The better the existing job description, it will improve the performance of employees of PT. Hayati Pratama Mandiri, 2) Job specifications have a positive and significant impact on employee performance. The more exact job specification which means that each job has the exact requirements specifications and employees obtained in accordance with the specified specifications, it will improve the performance of employees PT.Hayati Pratama Mandiri, and 3) Job evaluation has a positive and significant impact on employee performance at PT. Hayati Pratama Mandiri. The better performing job evaluation will improve employee performance.